The Presence of Diglossia in American-Based Talk Shows - Muhammad Ahsan Tampubolon; Nurmawati Nurmawati; Sukma Septian Nasution (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to find the types of diglossia and the factors of the use of language variations in the videos of â€œSteve Tv show, Netflix is a Joke, ABC, The Tonight Show Starring Jimmy Fallonâ€ on the YouTube channel. Diglossia is defined as a situation where two language variations occur at the same time. This is a content analysis and the data were taken from conversations in the video analyzed using Trudgill's theory. Further, factors of the occurrence of diglossia in the use of language variations are based on Yule's theory of diglossia. Using observation as main instrument of collecting data, all diglossia occurring in the selected videos are classified into high, medium, and low classes to be tallied to come to the final findings. The findings highlight that diglossia is found in six of the eight videos. The writers identified standard English as dominant on the Tonight Show Starring Jimmy Fallon's YouTube channel. While the use of non-standard English is more dominant in videos on the Steve Tv Show, Netflix is a Joke and ABC channel. The factor that causes a lot of language variation is the ethnic background where this factor is found on 3 YouTube channels, the age factor on 2 YouTube channels, the speech community factor on 2 YouTube channels, and the gender factor on 1 YouTube channel. From the two types of language variation and four of the five factors of diglossia found in the videos, high language variation and ethnic background factors are language variations and dominating factors